Expanding Audio Access to Mathematics Expressions by Students With Visual Impairments via MathML. Issue 1 (17th April 2017) - Frankel, Lois; Brownstein, Beth; Soiffer, Neil
Abstract: This report describes the pilot conducted in the final phase of a project, Expanding Audio Access to Mathematics Expressions by Students With Visual Impairments via MathML, to provide easy‐to‐use tools for authoring and rendering secondary‐school algebra‐level math expressions in synthesized speech that is useful for students with blindness or low vision. The pilot evaluated the authoring and speech‐rendition tools, including interactive navigation. Teachers participated in the portion of the study that evaluated the authoring tools. Secondary school students with blindness or low vision participated in the portion that evaluated the speech‐rendition and navigation tools, comparing those tools to each student's usual method (braille or print) for working with math. The teachers received an interactive authoring tutorial and the students received an interactive navigation tutorial before using the tools studied. Prior to the pilot, feedback studies on authoring and navigation gathered information that was used to fine‐tune the tutorials and the functionalities being evaluated. In the pilot we attempted to simulate a likely use‐case for each group. In the students' case, the tools for reading and navigating spoken mathematics were compared directly with the methods each student typically used for reading math (braille or print in a size appropriate for the student). Teachers and content providers were instructed to author math expressions that matched those used in the pilot instruments given to the students. The studies showed that the authoring tools were easy for teachers to use as intended and that little observable difference existed between students' success in answering math and math‐parsing questions when using the spoken math tools and their success in answering parallel questions posed in braille or print of appropriate size. Please see Appendix E for information on obtaining a version of this report that is fully accessible using the tools described. Abstract : Report Number: ETS RR‐17–13